Autour de Polanyi : vocabulaires, théories et modalités des échanges - Clancier, P.; Bresson, Alain (Editions De Boccard, 2005)
The varied questions which arise from the contributions made in this work provide a new modernity to Karl Polanyi and show the major interest in bringing together, as openly as his own, the various historical and economic specialties , Archaeological, ethnological, present in the House of Archeology and Ethnology of Nanterre. One of the most stimulating aspects of the contributions gathered here is the importance given to the presence of men, far beyond the simple equation of economic relations. These contributions sweep away a voluntarily vast field, from antiquity to the contemporary world. The historiographical dimension of Karl Polanyi's career is also present, through the contributions of Anne Chapman, who worked with him in South America, and his daughter, Kari Polanyi Levitt, specialist in development economics. Nathalie Zemon Davis, historian of societies in modern Europe, was asked to present the general conclusions of this symposium. Collection Conferences of Archaeology & Ethnology Maison René-Ginouvès , n o  1
Keywords: CHAPMAN, Anne; POLANYI LEVITT, Kari; ZEMON DAVIS, Nathalie

The Global Resistance Reader - Amoore, Louise (Psychology Press, 2005)
The Global Resistance Reader provides the first comprehensive collection of work on the phenomenal rise of transnational social movements and resistance politics: from the visible struggles against the financial, economic and political authority of large international organizations such as the World Trade Organization, World Bank and International Monetary Fund, to the much less visible acts of resistance in everyday life. The conceptual debates, substantive themes and case studies have been selected to open up the idea of global resistance to interrogation and discussion by students and to provide a one-stop orientation for researchers, journalists, policymakers and activists.
Keywords: GILL, Stephen; political science / globalization; political science / reference

Citizenship unbound: The global politics of neo-liberalism and labor migration - Barker, Isabelle Virginie; Cornell, Drucilla (2005)
This dissertation considers the status of citizenship in an era of neo-liberal globalization. Citing increased labor migration and the retreat of domestic social policies throughout the world as intersecting processes, I argue that narratives of national citizenship lie at the heart of this intersection, transformed by rapidly changing geopolitical conditions. Despite challenges, national citizenship remains a relevant political category, though reformulated along the lines of neo-liberal principles of privatization, market rationality, and individual responsibility. the politics and rhetoric surrounding the 1996 federal reforms of immigration and social policy in the United States serve as one example of this process. I further support my claim with an extensive illustration of the linkages between the restructuring of U.S. health care policy for senior citizens with the increased migration of women from the global South to provide low-wage direct care services for the aging population in the United States. I then evaluate the work of Martha Nussbaum, Amartya Sen and Thomas Pogge, arguing that their respective efforts fail to offer effective interventions into the fate of democratic citizenship in an era defined by expanding inequalities and shrinking public spaces. I conclude by bringing together the works of Karl Polanyi, David Held, and Hannah Arendt with feminist scholarship to develop a feminist theory of democracy and political membership for the twenty-first century. (Copyright applies to all Abstracts.)
Keywords: ARENDT, Hannah; HELD, David; NUSSBAUM, Martha; POGGE, Thomas; SEN, Amartya; citizenship; feminist theory; globalization; labour migration; political science; women's studies

The Economy as a Polity: The Political Constitution of Contemporary Capitalism - Joerges, Christian; Stråth, Bo; Wagner, Peter (Psychology Press, 2005)
The debate about so-called economic globalization has reached a new phase. The hegemony of neo-liberal thinking has ended, in the face of both the increased and increasingly effective resistance to the social consequences of neo-liberal market-making - rising inequality and insecurity throughout the world - and the visibly dysfunctional effects of lack of regulation - currency and stock market crashes, among others. Thus, the story about 'the rise and fall of market society', which was first told in these terms by Karl Polanyi sixty years ago, is about to receive a new chapter. In this light, this volume offers a novel perspective on the interaction between states and markets. In contrast to much of current theoretical wisdom, we hold, with Polanyi, that markets cannot even be consistently thought of as self-regulating. Markets are always constituted by framework conditions that cannot be set by the markets themselves. The range and scope of market rules requires some agreement, or at least acceptance, for economic exchange to be working at all; in democratic societies, these rules are at least theoretically always subject to political debate and decision. To put the issue in theoretical terms: even the most pure version of economic liberalism always entails at the same time a political philosophy. This volume, thus, proposes to understand contemporary capitalism by regarding the economy as a polity, as an arrangement that is always constituted by some collective agreements about its mode of operation. Such theoretical position on its own, though, is insufficient to explain the workings of capitalism once and for all. Historical experiences with capitalism have led to transformations that require new angles of analysis. It is in the nature of the struggles over the embedding of markets that their outcomes are subject to historical contingency and cannot be completely known beforehand. Beyond a review of the theoretical tools at hand, therefore, the analysis of the contemporary constellation of capitalism, also requires an understanding of its recent transformations. This is the second task to which this volume is devoted - through analyses of the current state of regulation of labour and money and through investigations of the historical development and novel forms of the mode of embedding markets. While focusing on the renewal of the analysis of contemporary capitalism, the volume also points to fruitful directions of institutional or policy change and provides perspectives for a much-needed political renewal, with a particular focus on the European Union as a novel polity embedding the European economy.
Keywords: business & economics; economic policy; free enterprise; public policy

Ancient Athens & modern ideology: value, theory & evidence in historical sciences : Max Weber, Karl Polanyi & Moses Finley - Nafissi, Mohammad (Institute of Classical Studies, School of Advanced Study, University of London, 2005)
Keywords: Athens (Greece); WEBER, Max, 1864-1920; civilization; classical civilization; classical philology; economic theory; economics; history / ancient / Greece; social science / sociology / general

Surviving Capitalism: How We Learned to Live with the Market and Remained Almost Human - Ringmar, Erik (Anthem Press, 2005)
Human life cannot be reduced to market transactions and human beings cannot only be treated as economic actors. When the power of the market increases, human beings will always try to protect themselves. Given the differences that exist in social and cultural traditions, these protective responses are likely to differ from one society to the other. This is why, even in a global market, diversity is always likely to persist. This book investigates the question of economic globalization - whether it is likely to lead to full convergence between political models and ways of life, or whether, even in a completely globalized world economy, there is likely to be scope for alternative solutions. But in a fully globalized world, how will we survive capitalism?
Keywords: economic globalization; globalization